Human Resource Management Practices and Employee Retention in the Nepalese Commercial Banks - Shrestha, Narendra Kumar; Joshi , Rajesh K. (Molung Educational Frontier, 2026)
This study investigates the impact of human resource management practices-compensation, training and development, and performance appraisal on employee retention in Nepalese commercial banks, moderated by work environment. More specifically, it investigates the connection between compensation and employee retention in the Nepalese commercial banks. Data were gathered via structured questionnaires from 384 employees, randomly sampled from 400 respondents across various banks. Regression analysis tested hypotheses on variable relationships. Findings show that performance appraisal positively and significantly affects retention, supported by a supportive work environment that motivates employees to remain. Work environment weakly moderates the training & development retention link. Compensation lacks significant impact, while training and development negatively influence retention, indicating misalignment with retention goals and a managerial emphasis on appraisal-driven motivation. Nepalese banks must redesign compensation and training policies to enhance long-term retention. This study investigates the connection between compensation and employee retention in the Nepalese commercial banks.